1997
DOI: 10.1200/jco.1997.15.2.491
|View full text |Cite
|
Sign up to set email alerts
|

Intensified and high-dose chemotherapy with granulocyte colony-stimulating factor and autologous stem-cell transplantation support as first-line therapy in high-risk diffuse large-cell lymphoma.

Abstract: This sequential scheme with intensified and high-dose chemotherapy with ASCT is feasible with moderate toxicity and may improve the outcome in high-risk DLCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…Thirty patients were treated with MACOP-B for 8 weeks, followed by intensification with a 3-day course of mitoxantrone 8 mg/m 2 plus high-dose Ara-C (2 g/m 2 every 12 h) 12 and granulocyte colony-stimulating factor to harvest PBPCs; conditioning regimen consisted of carmustine, etoposide, Ara-C and melphalan regimen followed by autografting. The policy of the centres involved in the two study protocols was to perform the autografting procedure with a minimum amount of 5 Â 10 6 CD34-positive cells/kg of recipient body weight.…”
Section: Treatment Planmentioning
confidence: 99%
“…Thirty patients were treated with MACOP-B for 8 weeks, followed by intensification with a 3-day course of mitoxantrone 8 mg/m 2 plus high-dose Ara-C (2 g/m 2 every 12 h) 12 and granulocyte colony-stimulating factor to harvest PBPCs; conditioning regimen consisted of carmustine, etoposide, Ara-C and melphalan regimen followed by autografting. The policy of the centres involved in the two study protocols was to perform the autografting procedure with a minimum amount of 5 Â 10 6 CD34-positive cells/kg of recipient body weight.…”
Section: Treatment Planmentioning
confidence: 99%
“…Pilot studies performed in specialized institutions are also warranted, and two merit more detailed discussion. The prospective cooperative trial reported by Vitolo et al 20 involved 50 patients with high-risk LCL. They were assigned to receive a programme which consisted of the following three phases: induction with 8 weeks of MACOP-B, intensification with high-dose cytarabine plus mitoxantrone and dexamethasone, and consolidation with BEAM therapy supported by ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…With a median followup of 32 months, OS and DFS were at 56% and 69%, respectively. 20 In another pilot study, the role of HDT with ABMT/ASCT during first CR or PR was assessed in 52 patients with poor-risk intermediate and high-grade lymphoma. The authors reported a 3-year DFS of 89% in the subset of patients with LCL, with 92% and 87% in the HI risk and H risk groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Table 1 Intensified sequential and high-dose chemotherapy with autologous transplantation in patients with lymphoma CR rate was 72.5% and actuarial 3-year EFS and overall survival was 40% and 48%, respectively. Vitolo et al 21 treated 50 high-risk DLCL patients with 8 weeks of induction MACOPB, followed by intensification with mitoxantrone (24 mg/m 2 ), cytarabine (12 g/m 2 ) and dexamethosone (24 mg/m 2 )(MAD). Thirty-nine patients (78%), achieving at least a PR, were consolidated with BEAM and PBPC support.…”
Section: Tandem Intensive Sequential Chemotherapy and Autologous Tranmentioning
confidence: 99%
“…This dose-intense strategy has been applied as both first-line and salvage therapy to poor risk patients Ͻ60 years (Table 1). [18][19][20][21][22] Two pilot studies of intensive sequential chemotherapy as first-line treatment in patients with aggressive NHL were conducted by Bouaddallah and colleagues. 23 For study ISC 92, patients received three cycles of high-dose CHOP (cyclophosphamide 3 g/m 2 , doxorubicin 75 mg/m 2 , vincristine 2 mg, and prednisone 60 mg/m 2 for 5 days) followed by three intensified stem cell supported cycles of high-dose CHOP with etoposide (300 mg/m 2 ) and cisplatin (100 mg/m 2 ).…”
Section: Tandem Intensive Sequential Chemotherapy and Autologous Tranmentioning
confidence: 99%